PEMETAAN TOPIK NILAI PUBLIK DALAM PENELITIAN - Wulandari, Rika; Rochima, Emma; Rianto, Yan; Endyana, Cipta (Direktorat Repositori, Multimedia, dan Penerbitan Ilmiah - Badan Riset dan Inovasi Nasional (BRIN Publishing), 2020)
This study aims to provide an overview of how public value research topics developed from 2001 to 2020. The mapping is expected to provide an overview of the development of research and provide input on the topic of public value research. This study uses the Scopus database from 2001 to 2020 to calculate citation analysis using the Publish or Perish (PoP) application and mapping publications using the VOSViewer application. From the analysis of literature studies based on the Scopus database from 2001 to 2020 272 journal articles are discussing public value research, it was found that the most publications were in 2019 (47 publications) and the highest research was dominated by the United Kingdom (65). For the highest number of citations, the publication with the title